LANGKAH-LANGKAH MENGETAHUI MAQASID ASY-SYARI’AH - Fatahuddin Aziz Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
Islamic law aims at users to get welfare and bless in life (maqasid asy-syari’ah). Here, the text of ‘illat law or hikmah (after law practice) discuss both users’ welfare and bless in life. Finally, ‘illat amar and nahyi, istiqrak, to keep Muhammad followers’ understanding, munasabah or syabah.